Characterization of Clinical Salmonella entericas Trains in Huzhou, China - Deshun Xu; Lei Ji; Wei Yan; Liping Chen (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Salmonella enterica subspecies enterica causes salmonellosis in humans and animals and is an important antecedent of food infections worldwide. This study collected 105 clinical S. enterica isolates from diarrhoea samples from six sentinel hospitals for active surveillance of foodborne diseases in Huzhou, China, between 2018 and 2020. These represented all the Salmonella isolates collected in Huzhou during that period. Methods. The isolates were characterized by serovar determination, antimicrobial susceptibility tests, and pulse-field gel electrophoresis (PFGE) typing. Results. The 105 Salmonella strains were mainly S. typhimurium (35.24%, 95% CI from 25.95 to 44.53%) and S. enteritidis (18.10%, 95% CI from 10.61 to 25.58%). Testing indicated that the resistance rate of the Salmonella strains ranged from 0.00% to 70.48%, and the highest resistance rate was for ampicillin (70.48%; 74/105), followed by tetracycline (67.62%; 71/105) and doxycycline (65.71%; 69/105). Following XbaI digestion, the 105 strains yielded 93 PFGE patterns, and 15 clones had similarity values >85.00%. Conclusions. Our analyses revealed the serovar distribution of isolates recovered from diarrhoea patients and the characteristics of resistant strains in Huzhou from 2018 to 2020. Our results highlight a serovar shift and a concerning number of multidrug-resistant (MDR) strains. Continued surveillance of Salmonella and their MDR profiles and efforts to control the rapid increase in antimicrobial resistance among Salmonella in Huzhou are needed.